Internet of things (IoT) imbedded point-of-care SARS-CoV-2 testing in the pandemic and post-pandemic era - Zhaoxi Wang; Simin Liu (Elsevier, 2022)
The outbreaks of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant in China have revealed a high rate of asymptomatic cases, making isolation and quarantine measures exceedingly difficult. Public health surveillance and intervention measures will require rapid and accurate testing preferably on-site using point-of-care tests (POCTs) technology for SARS-CoV-2 variants. However, delayed and/or inaccurate surveillance data is a major obstacle blocking the large-scale implementation of POCTs in curbing spread of infectious pathogens and reducing mortality during an outbreak. To determine levels of community transmission and timely strategies accordingly, highly sensitive and specific POCT embedded with the internet of things (IoT) technology could enable on-site screening and real-time data collection. A new Rapid Amplification with Sensitivity And Portability point-of-care test (RASAP-POCT) system based on thermal convection PCR is the first IoT-based isothermal nucleic acid amplification POCT, which can provide test results within 20-30 min using saliva and/or nasopharyngeal swab samples without nucleic acid extraction. With the IoT-imbedded feature, the RASAP-POCT system can be integrated easily and smoothly with China's existing mobile-phone-based contact tracing system, which has previously proved to be highly effective in maintaining the dynamic zero-COVID policy. Current regulatory guidelines and rules should be modified to accelerate the adoption of new technologies under an emergency use authorization (EUA).